The COVID-19 pandemic's impact on mental health care use among Norwegian students in higher education: a nation-wide register-based pre-post cohort study - Mari Grøsland; Vilde Bergstad Larsen; Anne Reneflot; Rannveig Kaldager Hart (BMC, 2022)
Abstract Background The COVID-19 pandemic, and its associated social distancing measures, gave profound changes to the everyday and academic life of students in higher education. The current study is the first to use nation-wide data to evaluate the long-term effect of the pandemic and its countermeasures on university students' mental health care use. Methods Using nation-wide individual-level data, we studied mental health consultations in primary care (data available from January 2017 to February 2022) and dispensed prescription drugs used to treat anxiety, depression, and sleep disturbances (data available from October 2018 to February 2021) for first-year undergraduate university students. We compared changes over time in mental health care use in a pandemic cohort (12,501 first-year students enrolled in 2019) to the same change in a pre-pandemic cohort (25,990 first-year students enrolled in 2017 and 2018). Event study and difference-in-difference models allowed us to separate the impact of the pandemic, experienced by the pandemic cohort only, from secular and seasonal changes experienced by all cohorts. Results The percentage of students with a mental health consultation temporarily decreased during the first period of strict social distancing measures in March 2020. At the end of the second round with strict measures in April 2021, the level of mental health consultations increased by 73% (95% CI 40-106.3). There was also a 42% (95% CI 5.7-79.5) increase in mental health consultations in November 2021. No similar increases were observed for dispensed prescription drugs between March 2020 and February 2021. Conclusions The COVID-19 pandemic was associated with increases in mental health consultations in primary care among students, especially during/after longer periods of strict social distancing measures. The benefits of social distancing measures in future pandemic preparedness should be weighed against the cost of potentially worsening mental health in vulnerable groups.